Mental Health Status of Late-Middle-Aged Adults in China During the Coronavirus Disease 2019 Pandemic - Zheng, Yong-Bo; Shi, Le; Lu, Zheng-An; Que, Jian-Yu; Yuan, Kai; Huang, Xiao-Lin; Liu, Lin; Wang, Yun-He; Lu, Qing-Dong; Wang, Zhong; Yan, Wei; Han, Ying; et al. (Frontiers in Public Health, 2021)
Background: The novel coronavirus 2019 (COVID-19) pandemic and related compulsory measures have triggered a wide range of psychological issues. However, the effect of COVID-19 on mental health in late-middle-aged adults remains unclear. Methods: This cross-sectional, web-based survey recruited 3,730 participants (≥ 50 years old) between February 28 and March 11 of 2020. The Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, Insomnia Severity Index, and Acute Stress Disorder Scale were used to evaluate depression, anxiety, insomnia, and acute stress symptoms. Multivariate logistic regression analysis was fitted to explore risk factors that were associated with the selected outcomes. Results: The mean age of the participants was 54.44 ± 5.99 years, and 2,026 (54.3%) of the participants were female. The prevalence of depression, anxiety, insomnia, and acute stress symptoms among late-middle-aged adults in China during the COVID-19 pandemic was 20.4, 27.1, 27.5, and 21.2%, respectively. Multivariable logistic regression analyses showed that participants who were quarantined had increased odds ratios for the four mental health symptoms, and those with a good understanding of the COVID-19 pandemic displayed a decreased risk for all mental health symptoms among late-middle-aged adults. In addition, participants with a low income and with a risk of COVID-19 exposure at work had a remarkably high risk of depression, anxiety, and acute stress symptoms. Conclusions: Mental health symptoms in late-middle-aged adults in China during the COVID-19 pandemic are prevalent. Population-specific mental health interventions should be developed to improve mental health outcomes in late-middle-aged adults during this public health emergency.